A capital market in Thailand - Robbins, Sidney M. (New York : Bank of Thailand)
This report is prepared and presented to the Bank of Thailand as part of the programme for capital market development.
osc 13/11/17
Loans
Keywords: Capital Market; Capital; Capital investment; Thailand